Inhibition of epidermal growth factor receptor suppresses parathyroid hormone‐related protein expression in tumours and ameliorates cancer‐associated cachexia. Issue 3 (4th April 2022) - Weber, Bahar Zehra Camurdanoglu; Agca, Samet; Domaniku, Aylin; Bilgic, Sevval Nur; Arabaci, Dilsad H.; Kir, Serkan
Abstract: Background: Lung cancer is the primary cause of cancer deaths worldwide. Activation of epidermal growth factor receptor (EGFR) leads to lung cancer progression and poor prognosis while involuntary weight loss remains a major problem. Tumour‐derived parathyroid hormone‐related protein (PTHrP) emerged as a potential mediator of cachexia. Here, we investigated the modulatory role of EGFR signalling in PTHrP (encoded by Pthlh ) gene expression and the impact of this relationship on cancer cachexia. Methods: Global gene expression profiles of Lewis lung carcinoma (LLC) cells were analysed. Pthlh mRNA levels were measured by qRT‐PCR in LLC cells treated with EGFR ligands and tyrosine kinase inhibitors (TKIs). LLC tumour‐bearing mice received EGFR TKI erlotinib for 7 days via intraperitoneal injection or oral gavage. Tumour Pthlh mRNA, weight of fat/muscle tissue, and grip strength were assessed. RNA‐seq data from The Cancer Genome Atlas and gene expression analysis tools were used to characterize expression profiles of PTHLH and EGFR along with correlation analysis of PTHLH with EGFR and transforming growth factor alpha ( TGFA ) in human lung cancer and head and neck squamous carcinoma (HNSC). Survival of lung squamous cell carcinoma (LUSC) and lung adenocarcinoma (LUAD) patients with EGFR gene alterations was analysed in regard to PTHLH expression. Results: Expression of EGFR ligands, EGFR itself, and PTHrP co‐clusters in LLC cells. Activation of EGFR signalling with its ligands significantly increases (3.8‐fold, P < 0.0005) while EGFR TKIs significantly decrease (90%, P < 0.0005) Pthlh mRNA levels in LLC cells. Pthlh mRNA drops 65–75% ( P < 0.0005) in tumours upon treatment of LLC tumour‐bearing mice with erlotinib while their muscle mass and grip strength increase (9.2% P < 0.05, 23% P < 0.005, respectively) compared with tumour‐bearing control mice. PTHLH is overexpressed in tumours of LUSC (45.8‐fold, P < 0.05) and HNSC (17.5‐fold, P < 0.05) compared with normal tissue. PTHLH expression correlates with EGFR and its ligand TGFA in both cancers (LUSC: n = 745, R = 0.32, P < 0.0001 and R = 0.51, P < 0.0001; HNSC: n = 545, R = 0.34, P < 0.001 and R = 0.50, P < 0.001, respectively). High PTHLH mRNA associates with poor overall survival in LUAD patients with activating EGFR mutations ( n = 40, log‐rank test, P = 0.0451). Conclusions: Epidermal growth factor receptor signalling regulates expression of cachexia mediator PTHrP. EGFR inhibition reduces PTHrP expression in LLC tumours and ameliorates cachexia in LLC tumour‐bearing mice.